Body Structural Description Impairment in Complex Regional Pain Syndrome Type I - Biran, Iftah; Book, Andrea; Aviram, Liron; Bregman, Noa; Bahagali, Einat; Tripto, Assaf (Frontiers in Psychology, 2022)
Background: Complex Regional Pain Syndrome (CRPS) is a clinical syndrome composed of chronic pain, motor impairment and autonomic dysfunction usually affecting a limb. Although CRPS seems to be a peripheral disorder, it is accompanied by parietal alterations leading to body-schema impairments (the online representations of the body). Impairments to body structural description (the topographical bodily map) were not assessed systematically in CRPS. A patient we encountered with severe disruption to her bodily structural description led us to further study this domain. Aims: To document aberrant body structural description in subjects with CRPS using an object assembly task. Methods: Body Schema Study: 6 subjects with CRPS-I and 6 age and sex matched healthy controls completed visual puzzles taken from WAIS-III and WAIS-R. The puzzles were either human body or nonhuman body objects. Mann-Whitney U-tests were performed to compare groups performances. Results: The CRPS group received lower scores for human body objects (u=3,p<0.05), whereas the nonhuman object scoring didn’t reveal significant differences between groups (u=9,p>0.05). Conclusions: CRPS subjects suffer from impaired body structural description which can take the form of body parts disassembly and body parts discontinuity. This impairment can serve as a nidus for aberrant psychological representation of the body.